Concurrent Initiation of Hepatitis C and Opioid Use Disorder Treatment in People Who Inject Drugs. (3rd February 2020) - Rosenthal, Elana S; Silk, Rachel; Mathur, Poonam; Gross, Chloe; Eyasu, Rahwa; Nussdorf, Laura; Hill, Kristi; Brokus, Christopher; D'Amore, Aaron; Sidique, Nadeera; Bijole, Phyllis; Jones, Miriam; et al.
Abstract: Background: People who inject drugs have a high prevalence of hepatitis C virus (HCV) and significant disease associated with drug use; however, HCV treatment often occurs in absence of interventions to address opioid use disorder and drug use–related harms. The impact of concurrent initiation of opioid agonist therapy (OAT) on HCV treatment and drug use outcomes is unknown. Methods: In this prospective, open-label, observational trial at a harm reduction organization's drop-in center in Washington, DC, 100 patients with chronic HCV infection, opioid use disorder, and ongoing injection drug use were treated with sofosbuvir-velpatasvir for 12-weeks and offered buprenorphine initiation. The primary end point was sustained virologic response (SVR), and secondary end points included uptake of and retention in OAT, change in risk behavior, and determinants of SVR. Results: Eighty-two patients (82%) achieved SVR, which was not associated with baseline OAT status ( P = .33), on-treatment drug use ( P >.99), or imperfect daily adherence ( P = .35) but was significantly associated with completing 2 or more 28-pill bottles of sofosbuvir-velpatasvir ( P < .001) and receiving OAT at week 24 ( P = .01). Of 67 patients not already receiving OAT at baseline, 53 (79%) started OAT. At week 24, 68 (68%) patients were receiving OAT. Receipt of OAT was associated with fewer opiate-positive urine drug screens ( P = .003), lower human immunodeficiency virus risk-taking behavior scores ( P < .001), and lower rates of opioid overdose ( P = .04). Conclusions: The Novel Model of Hepatitis C Treatment as an Anchor to Prevent HIV, Initiate Opioid Agonist Therapy, and Reduce Risky Behavior study demonstrates high uptake of buprenorphine collocated with HCV treatment, and it shows that concurrent initiation of OAT with HCV treatment can result in high rates of SVR while reducing risks associated with drug use. Clinical Trials Registration: NCT03221309. Abstract : Treatment of opioid use disorder collocated with hepatitis C virus (HCV) treatment results in high uptake of buprenorphine, and concurrent initiation of opioid agonist therapy with HCV treatment can increase sustained virologic response rates while reducing drug use–associated risks.